Rekonstruksi Fiqh dalam Merespon Perubahan Sosial - Harisudin, M. Noor (UIN Sunan Kalijaga, 2016)
Change is sina qua none in life. Fiqh respond to changes with the tools that have been prepared. Rigid nature onthe one hand and bending on the other side of the fiqh made itelastic in the face of various changes. No wonder if the views of fiqh changing following the change of date and place (salihun likulli zaman wa makan). Precisely there, fiqh finds himself as the legal formulationthat always compitable with all space and time.